Biodiesels powered in-cylinder common rail direct injection (CRDi) Assisted Homogeneous Charge Compression Ignition (HCCI) engine - Nagesh S.B.; N.R. Banapurmath; Chandrashekhar T.K.; S.V. Khandal (International Journal of Sustainable Engineering, 2021)
Experimental tests were performed on homogeneous charge compression ignition (HCCI) with in-cylinder direct injection (DI) of diesel, biodiesel of Ceiba Pentandra oil methyl ester (CPOME) and biodiesel of Acid oil methyl ester (ACOME). Initially some trial experiments were conducted at different fuel injection timing (IT) to distinguish the HCCI operation from common rail direct injection (CRDI) operation. For this, heat release rate (HRR) analysis, trial experiments were conducted for 40 % Load. The cool flame always started at about 20° before top dead centre (bTDC) showing HCCI operation started with fuel IT advancement of 50° bTDC and more. HCCI engine showed lowered peak HRR and retarded one. Higher injection pressure (IP) lowered oxides of nitrogen (NOx) due to lower HRR. NOx of 42 ppm, 36 ppm and 34 ppm were achieved with diesel, ACOME and CPOME respectively at IP 900 bar and IT of 80° bTDC in HCCI mode. Lower smoke of 9 HSU, 15 HSU and 17 HSU was achieved with diesel, ACOME and CPOME respectively at the same operating conditions. Overall, it could be concluded that, IP 900 bar and IT of 80° bTDC are the best operating conditions to reduce NOx and smoke with slightly lower brake thermal efficiency (BTE) in HCCI mode.